OBESITAS SEBAGAI IDE DALAM PENCIPTAAN SENI PATUNG - Idwan Rivai Hakim; Nooryan Bahari (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2022)
The sculpture is a work that is created through many gradual processes starting from the process of making the main master, then making molds, to the final casting and completion stages. Beyond that there are also sculptures made with chiseling or assembling techniques. Art works stems from human interest in the symptoms that occur in the community or the environment, and based on experiences that leave memory that supports the process of art, processing anxiety and curiosity are processed into a form of visualization of art, This work of sculpture takes the theme of obesity as a visual form, the form of obesity is related to people's views of their bodies, and also responses to attitudes carried out by obese people who are also used as ideas to visualize sculpture in the hope of providing another perspective on people with obesity in society.